KETERAMPILAN VERTICAL SPLIT ( Hubungan antara kelentukan togok dan keseimbangan dengan keterampilan vertical split pada atlet aerobic gymnastics klub Estafet Indonesia Fakultas Ilmu Keolahragaan Universitas Negeri Jakarta ) - CITRA RESITA (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2016)
This research aims to determine the relationship between flexibility togok and balance with Vertical Split skill of athlete aerobic gymnastics Club Estafet Indonesia. The sample consited of 25 people athlete aerobic gymnastics of club estafet indonesia selected total sampling. Data analysis was performed using the simple regression and correlation, multiple regression correlation. Results obtained from this study are: (1) by using the correlation, flexibility togok with vertical split skill with linear regression equation Y = 23,53+0,53X1. Correlation coefficient ry1 = 0,53 with tarithmetic = 3,29 and ttabel = 2,048. Because tarithmatic > ttabel with rejected Ho, correlation coefficient 0,53 is meant. (2) Â by using the correlation between balance with vertical split skill with linear regression equation Y = 25,57 + 0,45X2, correlation coefficient ry2 = 0,44 with tarithmatic = 2,59 and ttabel = 2,048, because tarithmatic > ttabel therefore rejected Ho, correlation coefficient 0,44 is meant. Â (3) by using the correlation flexibility togok and balance together with vertical split skill with Â double linear regression equation Y = 9 + 0,46X1 + 0,36X2, double correlation coefficient (Ry1-2) 0,64 with Farithmatic = 9,32 greater than from Ftabel 3,59 at the level of 0,05 it can be concluded that double correlation coefficient Ry1-2 = 0,64 is meant.